The Relationship between Extracurricular Participation and Students’ Non-Academic Achievement: Hubungan antara Partisipasi Ekstrakurikuler dan Prestasi Non-Akademik Siswa - Dea Syahfitri Sinaga; Topan Iskandar (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2024)
This study aims to examine the relationship between students’ participation in extracurricular activities and their non-academic achievement at the secondary school level. The study is grounded in the importance of holistic student development through non-academic activities such as sports, arts, and student organizations. A quantitative correlational research design was employed, involving students who had actively participated in extracurricular activities for at least one semester. Data were collected using a questionnaire to measure the level of students’ participation and teacher assessment records to evaluate non-academic achievement. Prior to analysis, the research instruments were tested for validity, reliability, normality, and linearity. The data were analyzed using the Pearson Product-Moment correlation technique. The results indicated that the majority of students demonstrated high (36%) to moderate (28%) levels of participation in extracurricular activities. Students’ non-academic achievement was predominantly categorized as good (40%) to very good (24%). The correlation analysis revealed a correlation coefficient of r = 0.726 with p = 0.000, indicating a positive and statistically significant relationship between participation in extracurricular activities and non-academic achievement. These findings suggest that increased involvement in extracurricular activities is associated with higher levels of non-academic achievement among students.